2001
DOI: 10.1111/j.1945-5100.2001.tb01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Itqiy: A metal‐rich enstatite meteorite with achondritic texture

Abstract: Abstract-Itqiy is a unique coarse-grained, metal-rich enstatite meteorite that was found in the Western Sahara and consists of two rocks together weighing 4.72 kg, which are both completely coated with fusion crust. We report results from our electron microprobe and instrumental neutron activation analysis techniques.Itqiy consists of subhedral, equigranular, millimeter-sized enstatite, -25 vol% of millimeter-sized kamacite and a few tiny intergrowths of sulfides and kamacite. Relic chondrules are absent. Pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 26 publications
4
52
0
Order By: Relevance
“…Metal also passes through silicate as a network of veinlets. Patzer et al (2001) also observed regions of sulfide and metal intergrowths consisting of intergranular assemblages of 3 different sulfides and metal globules. Different features in pyroxene indicate shock stages between 2 and 4 (Patzer et al 2001).…”
Section: Itqiymentioning
confidence: 82%
See 4 more Smart Citations
“…Metal also passes through silicate as a network of veinlets. Patzer et al (2001) also observed regions of sulfide and metal intergrowths consisting of intergranular assemblages of 3 different sulfides and metal globules. Different features in pyroxene indicate shock stages between 2 and 4 (Patzer et al 2001).…”
Section: Itqiymentioning
confidence: 82%
“…Patzer et al (2001) also observed regions of sulfide and metal intergrowths consisting of intergranular assemblages of 3 different sulfides and metal globules. Different features in pyroxene indicate shock stages between 2 and 4 (Patzer et al 2001). Itqiy enstatite shows no evidence for zoning and has Na 2 O, FeO and MnO abundances similar to EL chondrite pyroxenes, though CaO content is considerably higher than in ELs, whereas kamacite is compositionally identical to that of EH chondrites.…”
Section: Itqiymentioning
confidence: 82%
See 3 more Smart Citations